Escape routes desgin specifications and fire safety model for high-rise residential buildings - Yahya Mohamad Yatim (Penerbit UTM Press, 2016)
The book also contains a comprehensive simulation data, escape route design layout, human behaviour models and models of how a fire safety can be achieved in high-rise buildings. This information will be very helpful to those who are involved in building fire safety audit.